Cutaneous fungal infections in solid organ transplant recipients - Ana Gusmão Palmeiro; João Borges- (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Long-term exposure to immunosuppressive drugs is a significant risk factor for the development of both cancers and infections. Solid-organ transplant recipients benefit from dermatology follow-up, allowing early diagnosis and treatment of these conditions.   While there is abundant information on the development of cutaneous malignancies in these patients, there is still an underrepresentation in the literature regarding the prevalence, diagnosis, and treatment of cutaneous fungal infections. There is also more data available on cutaneous manifestations of systemic fungal infections than on superficial infections. Herein, the authors aim to present a short review of the most frequent primary fungal infections in this population, as well as to share some cases that presented to our dermatology outpatient clinic for solid organ transplant recipients.